The current state of research for psychobiotics use in the management of psychiatric disorders–A systematic literature review - Vasiliu, Octavian (Frontiers in Psychiatry, 2023)
The need to find new therapeutic interventions in patients diagnosed with psychiatric disorders is supported by the data suggesting high rates of relapse, chronic evolution, therapeutic resistance, or lack of adherence and disability. The use of pre-, pro-, or synbiotics as add-ons in the therapeutic management of psychiatric disorders has been explored as a new way to augment the efficacy of psychotropics and to improve the chances for these patients to reach response or remission. This systematic literature review focused on the efficacy and tolerability of psychobiotics in the main categories of psychiatric disorders and it has been conducted through the most important electronic databases and clinical trial registers, using the PRISMA 2020 guidelines. The quality of primary and secondary reports was assessed using the criteria identified by the Academy of Nutrition and Diabetics. Forty-three sources, mostly of moderate and high quality, were reviewed in detail, and data regarding the efficacy and tolerability of psychobiotics was assessed. Studies exploring the effects of psychobiotics in mood disorders, anxiety disorders, schizophrenia spectrum disorders, substance use disorders, eating disorders, attention deficit hyperactivity disorder (ADHD), neurocognitive disorders, and autism spectrum disorders (ASD) were included. The overall tolerability of the interventions assessed was good, but the evidence to support their efficacy in specific psychiatric disorders was mixed. There have been identified data in favor of probiotics for patients with mood disorders, ADHD, and ASD, and also for the association of probiotics and selenium or synbiotics in patients with neurocognitive disorders. In several domains, the research is still in an early phase of development, e.g., in substance use disorders (only three preclinical studies being found) or eating disorders (one review was identified). Although no well-defined clinical recommendation could yet be formulated for a specific product in patients with psychiatric disorders, there is encouraging evidence to support further research, especially if focused on the identification of specific sub-populations that may benefit from this intervention. Several limitations regarding the research in this field should be addressed, i.e., the majority of the finalized trials are of short duration, there is an inherent heterogeneity of the psychiatric disorders, and the diversity of the explored Philae prevents the generalizability of the results from clinical studies.